Handlebody decompositions of three-manifolds and polycontinuous patterns. (27th April 2022) - Sakata, N.; Mishina, R.; Ogawa, M.; Ishihara, K.; Koda, Y.; Ozawa, M.; Shimokawa, K.
Abstract : We introduce the concept of a handlebody decomposition of a three-manifold, a generalization of a Heegaard splitting, or a trisection. We show that two handlebody decompositions of a closed orientable three-manifold are stably equivalent. As an application to materials science, we consider a mathematical model of polycontinuous patterns and discuss a topological study of microphase separation of a block copolymer melt.